Odpowiedź:
[tex]\dfrac{6}{\frac{3}{4}}=6:\frac{3}{4}=\not6^2\cdot\frac{4}{\not3_{1}}=2\cdot4=8\\\\\\\dfrac{\frac{1}{2}}{2}=\frac{1}{2}:2=\frac{1}{2}\cdot\frac{1}{2}=\frac{1}{4}\\\\\\\dfrac{\frac{2}{3}}{\frac{3}{2}}=\frac{2}{3}:\frac{3}{2}=\frac{2}{3}\cdot\frac{2}{3}=\frac{4}{9}\\\\\\\dfrac{\frac{2}{3}}{\frac{2}{5}}=\frac{2}{3}:\frac{2}{5}=\frac{\not2}{3}\cdot\frac{5}{\not2}=\frac{5}{3}=1\frac{2}{3}\\\\\\\dfrac{\frac{4}{5}}{10}=\frac{4}{5}:10=\frac{\not4^2}{5}\cdot\frac{1}{\not10_{5}}=\frac{2}{25}[/tex]
[tex]2\cdot\dfrac{4}{\frac{1}{2}}=2\cdot(4:\frac{1}{2})=2\cdot(4\cdot2)=2\cdot8=16\\\\\\\dfrac{\frac{3}{4}}{5}:2=\frac{3}{4}:5:2=\frac{3}{4}\cdot\frac{1}{5}\cdot\frac{1}{2}=\frac{3}{20}\cdot\frac{1}{2}=\frac{3}{40}\\\\\\2:\dfrac{6}{\frac{4}{3}}=2:(6:\frac{4}{3})=2:(\not6^3\cdot\frac{3}{\not4_{2}})=2:\frac{9}{2}=2\cdot\frac{2}{9}=\frac{2\cdot2}{9}=\frac{4}{9}[/tex]